Big Cats - Shrivastav, Avadh B.; Singh, Keshav P. (IntechOpen, 2017)
In this book, the editors have reviewed the scientific articles from diverse group of scientists from all over the world who are actively participating in the wildlife conservation. Some of the important divisions incorporated in the book are conservation and population genetics, biodiversity, ecology, conservation physiology and evolution of big cats. The different chapters written by eminent scientists with their experience will provide an overview of the current information on conservation strategies and survival of big cats in different geographical zones around the world. The articles will also provide valuable information, on both free range and captive felines, to understand the present and future of the majestic species. The book will be useful to biologists, veterinary students, wildlife managers, researchers and also wildlife conservationists.